The effect of rootstocks on the fruit quality parameters of apple (Malus domestica Borkh.) - Racskó, József; Soltész, Miklós; Budai, Lejla; Szabó, Zoltán; Farkas, Ervin; Nagy, János; Nyéki, József (Acta Agraria Debreceniensis, 2005)
The authors studied the effect of rootstocks with different growing vigour on fruit quality of different cultivars. Research results shows that best fruit diamter and fruit weight of all cultivars are for M9 rootstock. Similar tendency was found in skin colour, but in the case of Granny Smith, MM106 rootstock is more favourable because the green skin colour is necessary for the consumers’ acceptance. Seedling rootstok has some unfavourable effects on fruit quality, thus its usage is not expedient.